Impact of the Free-Pelvis Innovation in Very Rigid Braces for Adolescents with Idiopathic Scoliosis: Short-Term Results of a Matched Case-Control Study - Stefano Negrini; Fabrizio Tessadri; Francesco Negrini; Marta Tavernaro; Andrea Zonta; Fabio Zaina; Sabrina Donzelli (MDPI AG, 2022)
We introduced pelvis semi-rigid material (ethylene vinyl acetate) (Free-Pelvis) to improve the comfort and adaptability of very rigid braces (VRBs) for adolescents with idiopathic scoliosis (AIS), but this can also negatively impact the corrective forces on the trunk. Study Design: This was a matched retrospective cohort study. The inclusion criteria were AIS, age 10-16, VRB 23 h/day, X-rays available, primary curve 36°-65°, and angle of trunk rotation 7-23°. The cases were Sforzesco VRB with Free-Pelvis (FPB). The controls included classical Sforzesco VRB matched for Risser (range 0/4), menarche age (10/15), weight (33.5/83 kg), height (140/180 cm), BMI (13.5/29 kg/sqm), aesthetics (TRACE 4/12), plumbline distances (S1: −60/35; C7 + L3: −10/115 mm), and referred brace use (22/24 h/day). Statistics: predictors of the results have been tested with linear and logistic regression according to the outcome variable type. We performed logistic regression for improved vs. worsened. The explanatory variable was brace type. We included 777 VRB and 25 FPB, age 13 ± 1, 47° ± 8° Cobb, and 11% men. The few baseline statistical differences were not clinically relevant. We achieved in-brace corrections of 15.2° ± 7.7° and 17.4° ± 6.5° for VRB and FPB, respectively (p = 0.21); out-of-brace corrections at 5 ± 2 months were 7.8° ± 0.2° for VRB and 8.1° ± 1.3° for FPB (p = 0.83). The type of brace did not influence the Cobb angle at either time interval or affect the odds of improvement. Free-Pelvis innovation, introduced to improve comfort and adaptability, does not change the in-brace or short-term results of classical VRB and consequently can be safely applied.